Phosphorylcholine- and cation-bearing copolymer coating with superior antibiofilm and antithrombotic properties for blood-contacting devices. Issue 36 (19th August 2020) - Zhang, Fanjun; Yang, Li; Hu, Cheng; Li, Linhua; Wang, Jingyu; Luo, Rifang; Wang, Yunbing
Abstract : The phosphorylcholine- and cation-bering copolymer coating endowed the blood-contacting devices with superior antibiofilm and antithrombotic ability. Abstract : Nosocomial infections resulting from bacterial attachment on blood-contacting medical devices, as well as biofilm and thrombus formation caused by fibrin crosslinking and platelet accumulation/activation are a major health concern and may lead to severe morbidity and mortality. Therefore, there is an urgent need to develop facile and efficient surface coatings with both antibiofilm and antithrombotic properties to prevent medical-device associated infections as well as thrombus formation. In this study, the copolymers containing quaternary ammonium (QA) and phosphorylcholine (PC) groups were synthesized through traditional free-radical copolymerization. The cationic group of QA provides bactericidal properties, and the cell membrane-mimicking group of PC provides antithrombotic and antifouling properties. Long-term stability of the copolymer coating was achieved via simple dip coating. X-ray photoelectron spectroscopy and water contact angle measurement demonstrated that the QA and PC groups possessed inversion properties once in contact with water allowing for long-term stability. Scanning electron microscopy and confocal laser scanning microscopy demonstrated that the copolymer coating could maintain antibiofilm properties for one week in a nutrient-rich environment. Furthermore, the copolymer coating significantly decreased platelet adhesion/activation and did not cause hemolysis. The ex vivo blood circulation showed no thrombus formation which confirmed the excellent antithrombotic property of the copolymer coating. Such coatings that maintain high cell viability and exhibit both antibiofilm and antithrombotic properties present potential applications for blood-contacting devices.